2022
DOI: 10.3389/fonc.2022.839516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enteral Nutrition on Patients With Oesophageal Carcinoma Treated With Concurrent Chemoradiotherapy: A Prospective, Multicentre, Randomised, Controlled Study

Abstract: BackgroundThe oesophageal carcinoma patients show high incidence of malnutrition, which negatively affects their therapy outcome. Moreover, benefits of enteral nutrition remain to be studied in details in these patients. Therefore, we set to assess the effects of enteral nutrition on the nutritional status, treatment toxicities and survival in the oesophageal carcinoma patients treated with concurrent chemoradiotherapy (CCRT).Materials and MethodsEligible patients were randomly assigned to either the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A phase III, randomized, controlled trial showed that early nutrition and psychological intervention could reduce the mortality risk of patients with advanced esophageal cancer by 32% [ 30 ]. A prospective, multicenter, randomized study showed that whole-course nutrition management is helpful to maintain the weight and nutritional status of esophageal cancer patients receiving concurrent radiotherapy and chemotherapy and improving their treatment tolerance and short-term prognosis [ 31 ]. Nutritional support may improve the prognosis of pancreatic cancer, which deserves further attention and research.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III, randomized, controlled trial showed that early nutrition and psychological intervention could reduce the mortality risk of patients with advanced esophageal cancer by 32% [ 30 ]. A prospective, multicenter, randomized study showed that whole-course nutrition management is helpful to maintain the weight and nutritional status of esophageal cancer patients receiving concurrent radiotherapy and chemotherapy and improving their treatment tolerance and short-term prognosis [ 31 ]. Nutritional support may improve the prognosis of pancreatic cancer, which deserves further attention and research.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the results of previous studies conducted in China, which indicated that a better nutritional status can help reduce the incidence of complications. [21][22][23][24]46] Furthermore, as expected, the length of hospital stay and in-patient costs both decreased in the intervention group owing to better nutritional status and fewer complications.…”
Section: Discussionmentioning
confidence: 79%
“…Statistically significant differences were observed between the intervention and the control groups. Compared with the control group, the average length of hospital stay decreased by 12 days [47 (40, 50) vs 35 (23,40), P = .001], and in-patient expenses decreased by 20,504 CNY in the intervention group (P = .004).…”
Section: Incidence Of Complications and Clinical Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…These results suggest that artificial nutrition, either supplements, enteral or parenteral nutrition, should be frequently considered, proposed and implemented in patients with digestive cancers in order to meet protein targets. Supporting this approach, in malnourished patients with oesophageal carcinoma and treated with concurrent chemoradiotherapy, the use of enteral nutrition yielded to less decrease in body weight, serum albumin and haemoglobin levels, a lower incidence rate of grade !3 myelosuppression and infection, and a higher completion rate of concurrent chemoradiotherapy than those in the control group [12]. Of interest, overall and progression free survival were significantly extended in patients with more severe malnutrition, that is, Patient Generated-Subjective Global Assessment (PG-SGA) ¼ C.…”
Section: Recommended Daily Protein Intake and Adequacy In Patients Wi...mentioning
confidence: 99%